Within Four Walls - Alajbegovic, Zemira (Zank ; VPK ; TV Slovenija, 1999)
Soros Documentary Fund In the documentary "Within Four Walls”, Slovene women who have escaped from violence in their own families and sought help in local shelters tell their stories. With covered faces they talk about years of abuse, violence, rape, loneliness and isolation. The filmmakers have visited the refuge for women and children, the victims of violence, the Center for Social Work, the group for non-violent communication - in which men try to change their violent behaviour, and met with historians and anthropologists to understand the issue of domestic violence.